Effect of Different Deposition Power of In2O3 Target on the Characteristics of IGZO Thin Films Using the Cosputtering Method. (10th August 2014) - Hung, Shang-Chao; Lam, Kin-Tak; Yang, Cheng-Fu; Liou, Yu-Jhen
Abstract : The (In, Ga, Zn)O x (IGZO) thin films were deposited on glass substrates using cosputtering method in radio frequency magnetron sputtering system. Zn2 Ga2 O5 (Ga2 O3 -2 ZnO, GZO) and In2 O3 ceramics were used as targets and dual guns were used to deposit the IGZO thin films. Deposition power of GZO target was 80 W and deposition power of pure In2 O3 target was changed from 70 W to 100 W, and the deposition time was 30 min. The effect of deposition power of In2 O3 target on the crystalline, surface, electrical, and optical properties of the IGZO thin films was investigated at room temperature in a pure Ar atmosphere. The cosputtered IGZO thin films showed a very smooth and featureless surface and an amorphous structure regardless of the deposition power of In2 O3 target due to the room temperature sputtering process. However, the cosputtered IGZO thin films exhibited transparent electrode properties because they had high transmittance ratio and low resistivity. The value variations in the optical band gap ( E g ) values of the IGZO thin film were evaluated from the plots of ( α h ν ) 2 = c ( h ν - E g ) . We would also show that the deposition power of In2 O3 target would have a large effect on mobility and E g value of the IGZO thin films.